Mapping Research Trends on MSMEs in Tourism Villages through Bibliometric Analysis - Riani Prihatini Ishak; Julia R. Skawanti; Samuel Samuel; Aditya Sugih Setiawan (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Tourism villages have increasingly become a strategic approach to promoting inclusive economic growth, cultural preservation, and sustainable development, with Micro, Small, and Medium Enterprises (MSMEs) serving as key actors in strengthening local economies. However, studies examining MSMEs in tourism villages within the context of sustainable tourism and community empowerment remain fragmented, and a comprehensive bibliometric mapping of this field is still lacking. This study aims to map and analyze publication trends, thematic structures, and emerging research themes on MSMEs in tourism villages within the context of sustainable tourism and community empowerment using a bibliometric approach. Employing a descriptive quantitative design with a bibliometric approach, this study analyzed 233 journal articles published between 2013 and 2023, retrieved from the Dimensions database and selected SINTA-accredited journals. Data were examined using VOSviewer through co-occurrence, overlay, and density visualizations to identify research trends and thematic evolution. The findings reveal increasing scholarly attention to the topic, particularly in the post-pandemic period, with dominant themes encompassing community empowerment, business model innovation, digital transformation, and capacity building. The study concludes that the literature has increasingly shifted toward themes of community empowerment, digital transformation, business model innovation, and multi-stakeholder collaboration, indicating the growing importance of sustainability-oriented approaches in MSME development within tourism villages.